Strategy Management - Grolier business library (United States of America : Grolier Incorporated, 1990)
Strategy management is a strategic business planning seen as partial solution to management problem, in order to significantly and permanently assist an organization.
Includes bibliographical and index.
gp 13/06/2019
Loans